Fracture Nasal Bone: Causes, Presentation and Management in a Tertiary Care Center in Nepal - Mahaseth, Rajeev K; Gurung, Urmila; Thapa, Narmaya; Pradhan, Bibhu; Kharel, Bijaya (Journal of Institute of Medicine Nepal, 2020)
Introduction Fracture of nasal bone, the commonest facial fracture is frequently encountered in ENT practice. This study was conducted to assess the causes, presentation and management of fracture nasal bone in a tertiary care center. Methods A retrospective chart review was done of patients admitted from August 2017 to July 2019 for management of isolated nasal bone fracture in the department of ENT and Head and Neck Surgery, Tribhuvan University Teaching Hospital. Results Thirty-five patients (31 males and 4 females) of 13 to 86 years (mean age 26 years) underwent closed reduction of fracture nasal bone. The injury was sustained following physical assault in 13/35 (37%), fall from height in 10/35 (29%), road traffic accident in 8/35 (23%) and sports injury in 4/35 (11%). Pain, epistaxis, swelling over nasal dorsum, nasal deformity and wound were the presenting symptoms which most often occurred in combination. Close reduction was done under local anesthesia in 28/35 (80 %) and under general anesthesia in 7/35 (20%). The time between trauma and closed reduction ranged from 1 to 16 days with a mean of 6.2 days. Conclusion Nasal bone fracture needing reduction was common following physical assault in males predominently of 21 to 30 years. A combination of pain, epistaxis and nasal deformity was the commonest presentation. Closed reduction of fracture under local anesthesia within 16 days of trauma was the usual practice.